HUBUNGAN MEKANISME KOPING DENGAN TINGKAT KECEMASAN PASIEN COVID-19 DI RUMAH SAKIT ISLAM IBNU SINA PEKAN BARU - MERSI EKA PUTRI; SALMI WITRI; JUVENTI ADE FITRI; RAHMANIZA RAHMANIZA (Jurnal Ilmu Keperawatan, 2021)
Covid-19 will have an impact on the psychological of the patient, one of the psychological problems is anxiety. The right coping mechanism will have a good impact on the patient. this study aims to determine the relationship between the mechanism of coping with the level of anxiety of patients Covid-19 at Ibnu Sina Pekanbaru Islamic Hospital. Design of the study This is a study quantitatively by using design research analytic with design cross-sectional. Research is carried out carried out at Ibnu Sina Pekanbaru Islamic Hospital with 56 respondents. Method of taking a sample that used is purposive sampling. Tools measure that is used is the questionnaire. Data analysis consists of univariate analysis and bivariate with test Chi-square. Results of the study showed that respondents aged 56-75 years (elderly end) as many as 41 respondents (73,2%), respondents high school as much as 19 respondents (33,9%), respondents worked privately as much as 26 respondents (46,4%), and respondents manifold sex women as much as 35 respondents (62,5%), Respondents with maladaptive coping mechanism 42 respondents (75,0%), respondents with moderate anxiety 38 respondents (67,9), and there is a significant relationship between coping mechanisms and anxiety levels in Covid-19 patients, where p value <0.05 is 0.040. Results of the study is expected as a material input for Ibnu Sina Pekanbaru Islamic Hospital in order to improve the quality of care of health especially care nursing are associated with patient Covid-19. Words key : mechanisms of coping, anxiety, Covid-19.